Análisis de los Procesos Desarrollado, para la Inclusión de la Comunidad Indígen Embera Chamí Asistenta una Institución Educativa del Departamento del Quindío. (2016)
One of the features of the School in Colombia is to ensure the inclusion of education population. Therefore, public institutions of the country should implement actions to guarantee the right to inclusion. From this premise, Rural Educational Institutions of the country implemented the so-called "New School" model UN aims to give a room the enormous diversity of the population. This work itself focused on the analysis of the processes performed to generate an Inclusive Education in the Educational Institution Laurel, in the municipality of Quimbaya Quindio. This institution stands out in the department to provide special education for the indigenous community Embera Chami, to have the presence of etnoeducador and its own headquarters for Indian students. Descriptive institution in frames is subject to the inclusive models of the New School, post-primary and etnoeducación the latter Analysis Since the inclusion of the indigenous community center said. As part of the investigation, a review of institutional documents, visions and relations of teachers, parents and students, as well as a s processes carried out by teachers in their classrooms and relations with the indigenous community of executives and teachers realize , from the characteristics that mark the inclusion and cultural relations, it is so what was evidenced While a written level has mentions relevant for the inclusion of the population, in terms of execution son Questions not you contextualized marked by authoritarian relationships eventually generate a invisibility and Standardization of the community include aims, it is concluded that having an institutionalized process and recognized for inclusion determined Population without assures that it is in the real sea plane executed Depth meriting Inclusive Education .